Pre-stressed concrete railway sleepers type B70W-60: requirements, technology of production, numerical modelling and calculations of immediate technological shortening - Betlej, Michał; Ciurej, Henryk; Chudyba, Łukasz (Archives of Civil Engineering, 2026)
A railway sleeper is one of the basic elements of track that directly impacts traffic safety. Therefore is essential a high quality requirements for the sleepers. This thesis shortly demonstrate requirements for prestressed concrete railway sleeper and present production technology and the method of prestressing of sleeper B70W-60. Goal of this paper covers the numerical modelling of the sleeper and determination of immediate strain and shortening directly after prestress activation. Longitudinal shortening the sleeper immediately after releasing tension bolts, manifest itself in separating concrete from mould walls. Measuring the width of this separation is a useful indicator value – if it is too high, it may mean that there are technological process errors or an internal defect of an individual sleeper. Therefore, the numerical estimation of the separation width is a part of design process.